MORFOSTRATIGRAFI TUF IGNIMBRIT MANINJAU DI NGARAI SIANOK, DUSUN BELAKANG BALOK-BUKITTINGGI, SUMATERA BARAT - Soemantri Poedjoprajitno (Pusat Survei Geologi, 2008)
The ignimbtrite plato of Sianok Valley at Belakang balok Village was produced by two periods of Maninjau volcanic eruptions. The two eruption periods are separated by fluvio volcanic deposits, consisting of very qoarse sand and conglomerate. The two periods pyroclatic deposits at containing pumice and locally several coal.Â These pyroclatic deposits were faulted and formed terrace morphology. The Sianok Valley is considered as an effect of the reactivation of basement fault throughting the ignimbrite deposits.Â Keywords:morphostratigraphy , Maninjau pumice tuf, terrace, fault, plato